Recent agricultural policy developments and options in Bulgaria - Mergos G.; Stoforos C.; Mishev P.; Ivanova N. (Selected readings on economies in transition, 2000)
The paper presents a brief picture of the country's reform process and the main developments of its agricultural sector. Then it develops a multi-market, dynamic, partial equilibrium and synthetic type model for exploring price and trade policy measures in Bulgaria. The model is used for undertaking price and trade policy analysis for the period up to 2002 with 1997 as a base year examining scenarios such as full price liberalization and adoption of CAP-type policies.